Coupled π-conjugated chromophores: Squaraine dye dimers as two connected pendulums. (February 2015) - Kuster, Simon; Geiger, Thomas
Abstract: Intense absorption ability in the near infrared (NIR) region is mandatory for many technologies and applications. The design thereof is however quite complex since only a few dye classes show these properties. Polymeric squaraine dyes have them however they are mostly hardly soluble. Herein four dimeric soluble and easy to prepare squaraine dye dimers are reported with absorption maxima between 679 and 805 nm. The synthesis, characterisation, the determination of the physicochemical properties and the in silico study of the calculated molecular geometry, the molecular orbitals, and the calculated total charge density surface were compared. The coupling of the two chromophores is concluded as a matter of the distance in-between, the π-electron system of the bridge, the spatial orientation thereof, and the spatial orientation of the electronic transition moment. The closer the two chromophores were and the less out-of-plane elements the bridge has, the smaller the optical band gap is. Graphical abstract: Highlights: Are the optical properties interfering in two covalently connected squaraines? Synthesis of two novel bridged squaraine dye dimers. The physicochemical properties indicated an extraordinary coupling. Molecular modelling explains the outstanding bathochromic shift.